ADVANCEMENTS IN VESTIBULAR PHYSIOTHERAPY: A COMPREHENSIVE REVIEW - Aleksandar Andreev; Stefka Mindova (Peytchinski Publishing, 2024)
Purpose. Vestibular disorders pose significant challenges to individuals' daily functioning and quality of life, necessitating effective management strategies. This comprehensive review explores modern advancements in vestibular physiotherapy, encompassing assessment techniques, intervention modalities, technological innovations, and interdisciplinary collaboration. Material/Methods. Accurate assessment and diagnosis are essential for tailoring treatment plans to individual needs. Traditional clinical tests, such as the Dix-Hallpike maneuver and head impulse test (HIT), remain foundational while emerging technologies like video head impulse testing (vHIT) offer objective measures of vestibular function. Treatment of benign paroxysmal positional vertigo (BPPV) often involves canalith repositioning maneuvers (CRM), with recent modifications and augmented reality applications enhancing efficacy and patient comfort. Results. Vestibular rehabilitation therapy (VRT) plays a pivotal role in promoting central nervous system compensation for vestibular deficits. Incorporating exercises targeting balance, gaze stabilization, habituation, and sensory integration, VRT facilitates symptom reduction and functional improvement. Technological innovations, including virtual reality (VR) systems and smartphone applications, augment traditional VRT approaches, enhancing engagement and accessibility. Moreover, interdisciplinary collaboration among healthcare professionals ensures comprehensive management of vestibular disorders. Physiotherapists, otolaryngologists, neurologists, audiologists, and psychologists collaborate to deliver personalized care and empower patients through education and counseling. Conclusions. Modern vestibular physiotherapy offers a multifaceted approach to address the complex needs of individuals with vestibular disorders. By leveraging evidence-based practices, integrating technological solutions, and fostering interdisciplinary partnerships, healthcare providers can optimize treatment outcomes and enhance patients' overall well-being.